Selective serotonin-reuptake inhibitor and norepinephrine dopamine reuptake inhibitor antidepressants do not affect natural killer cell activity in vitro - Gauer,Gabriel J. Chittó (2009)
OBJECTIVE: This study aims to evaluate the citotoxic activity of two commonly used anti-depressants: paroxetine and bupropion. We also evaluated the in vitro natural killer activity (NKA) after incubating the blood samples with the antidepressants. METHODS: Peripheral blood samples from 15 healthy volunteers were collected and the mononuclear cells (PBMCs) were isolated and incubated for 24h with (or without = control cells) paroxetine and bupropion, in concentrations of 30, 100 and 1000 ng/ml. After the incubation period in both groups, the amount of dead cells was calculated using trypam blue technique. NKA was evaluated using the classic51Cr release assay. CONCLUSIONS: PBMCs dead cells occurred in both groups and in proportion to all pharmacological concentrations. Nevertheless, the NKA was not affected, even with the reduction in the number of effective cells.